种替卡格雷中间体的制备方法 (2018)
本发明涉及种替卡格雷中间体的制备方法，具体涉及种作为药物中间体的式（2）所示的化合物或其盐的制备方法，以及该化合物（2）或其盐在制备三唑并嘧啶类化合物中的用途。本发明提供的方法合成工艺简单，大大简化了反应后处理，使用本发明提供的技术方案制备三唑并嘧啶类化合物时，整个合成工艺易于进行，并使得制备三唑并嘧啶类化合物的中间体的产率大大提高，特别适合于工业化生产。 The invention relates to a preparation method of a ticagrelor intermediate, specifically to a preparation method of a compound or its salt which is used as a medical intermediate and is as shown in the formula (2) and an application of the compound (2) or its salt in preparation of a triazolopyrimidine compound. According to the method provided by the invention, synthetic process is simple and reaction post-treatment is greatly simplified. By the technical scheme for preparation of the triazolopyrimidine compound, the whole synthetic process is easy to carry out, and yield of the intermediate for preparation of the triazolopyrimidine compound is greatly increased. The preparation method is especially suitable for industrial production.